2021
DOI: 10.3390/microorganisms9081757
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics of Fungi Associated with Healthy and Diseased Pinus sylvestris Needles in Northern Europe

Abstract: The relationship between the ecological success of needle pathogens of forest trees and species richness of co-inhabiting endophytic fungi is poorly understood. One of the most dangerous foliar pathogens of pine is Dothistroma septosporum, which is a widely spread threat to northern European forests. We sampled two Pinus sylvestris sites in Estonia and two in Norway in order to analyse the relations between the abundance of D. septosporum and overall fungal richness, specific fungal species composition, time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
(105 reference statements)
2
5
0
Order By: Relevance
“…The PCR products were sequenced using PacBio platform at the University of Oslo, Norway. PacBio has been recently used successfully in metabarcoding analysis of microorganisms in different plant, tree, and insect species, with the lesson that the long DNA barcodes (500–1500 bp) enabled by the platform substantially improve the resolution in species identification ( Loit et al, 2019 ; Tedersoo and Anslan, 2019 ; Tedersoo et al, 2019 ; Agan et al, 2020 , 2021 ; Jürisoo et al, 2021 ). The primer ITS1catta was originally designed to differentiate H. albidus from H. fraxineus , and to avoid amplification of plant DNA and the long intron in the 3′ end of the rRNA 18S gene of Hymenoscyphus species (see Tedersoo and Anslan, 2019 ; Agan et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The PCR products were sequenced using PacBio platform at the University of Oslo, Norway. PacBio has been recently used successfully in metabarcoding analysis of microorganisms in different plant, tree, and insect species, with the lesson that the long DNA barcodes (500–1500 bp) enabled by the platform substantially improve the resolution in species identification ( Loit et al, 2019 ; Tedersoo and Anslan, 2019 ; Tedersoo et al, 2019 ; Agan et al, 2020 , 2021 ; Jürisoo et al, 2021 ). The primer ITS1catta was originally designed to differentiate H. albidus from H. fraxineus , and to avoid amplification of plant DNA and the long intron in the 3′ end of the rRNA 18S gene of Hymenoscyphus species (see Tedersoo and Anslan, 2019 ; Agan et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The lack of a difference in species richness between leaf flushes in our study contrasts with the two previous studies on this topic, which all found a higher species richness on leaves from the first flush than on leaves from the second flush. Unterseher et al ( 2018 ) found a higher species richness of foliar fungi in leaves from the first flush than in those from the second flush in tropical plants in Thailand, and Agan et al ( 2021 ) found a higher species richness in Pinus sylvestris ‐needles from the current year than in needles produced in previous years in Estonia and Norway. While very speculative, this might suggest that there are differences in the effects of the production of multiple leaf flushes on the species richness of the foliar fungal community between tropical and temperate regions, or between coniferous trees (where leaves from different years co‐exist) and deciduous trees.…”
Section: Discussionmentioning
confidence: 99%
“…These fungi are known to cause plant diseases, induce plant defences in response to biotic and abiotic stresses (Arnold et al, 2003 ; Jaber & Enkerli, 2017 ) and influence leaf senescence and decomposition (Vacher et al, 2016 ). While these fungi are crucial for plant health and ecosystem functioning, we lack insights into the patterns and drivers of within‐ and among‐tree variation in the foliar fungal community (Agan et al, 2021 ; Allen et al, 2020 ; Millberg et al, 2015 ; Moler & Aho, 2018 ; Piepenbring et al, 2015 ; Sokolski et al, 2017 ; Terhonen et al, 2011 ; Unterseher et al, 2018 ). One factor that might explain within‐tree variation in the foliar fungal community is the co‐existence of leaves from different leaf flushes within individual trees.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations